A moda como imagem onírica: uma análise benjaminiana da revista Harper‟s Bazaar - Gavino, Carolina Fabian Sato (2016)
This research assigns the perception of Harper‟s Bazaar magazine in Brazil as a bold and dialectic image of our time. The main objective of the dissertation is to track how fashion is represented on the magazine made itself as merchandise and phantasmagoria fetish since its foundation until today. In order to validate it, we use support in the Walter Benjamin‟s studies inserted in The Arcades Project and Selected Writings. According to the historical context of the time period preceding the North American magazine debut in 1867, birth of industrial capitalism and rise of bourgeoisie class in the heart of society. In that way expanding the beginning of Haute Couture and media in the fashion industry in Europe and United States. Adorno‟s and Horkheimer‟s study about the concept of Iluminism was summoned in this section of our work for elucidation of how the 19th century upper class men thinks. The second chapter of this investigation trusts Benjamin‟s writings in The Arcades Project. Susan Buck-Morrs (2002) and Willi Bolle (2000) analysis that set up a significant part of the state of art about The Arcade Project, were consulted to develop conclusions about fashion and Bazaar‟s magazine as dream imagery. In the third chapter, it is possible to add up the existence of fashion editorial and photography support as a historical object in Brazil. For theoretical guidance, we employ Trivinho (2012) analysis about Glocal and Benjamin‟s rehearsal about aura The Work of Art in the Age of Mechanical Reproduction. This is research importance is due to the fact that the brazilian Harper‟s Bazaar was short-lived, launched only in 2011, even so it is one of the most dated American fashion magazine. Furthermore, we highlight the absence of a review of this type of media in the field of communication and semiotics